NURSING ASSISTANCE TO PATIENTS WITH TUBERCULOSIS AND COVID-19 IN VULNERABLE AREAS: NURSING ASSISTANCE TO PATIENTS WITH TUBERCULOSIS AND COVID-19 IN VULNERABLE AREAS - Sarmento, Joingrid Maria de Assis; Medeiros, Renata Lívia Silva Fonseca Moreira de; Feitosa, Ankilma do Nascimento Andrade; Elias, Kaique Lopes; Souza, Anne Caroline de; Silva, Talina Carla da (Brazilian Journal of Production Engineering, 2020)
Objective: Investigate the challenges in nursing care for patients with tuberculosis and covid-19 in vulnerable areas. Methods: Integrative review of literature with base in the leading question: What are challenges in the nursing assistance for person with tuberculosis living in vulnerable communities, given the high level of exposure to the covid-19 pandemic? The searches were in the scientific data bases: BVS, LILACS and MEDLINE to collect information about the nursing assistance to patients with tuberculosis and covid-19 in vulnerable areas. This present review consists of 04 scientific articles. Results: The processes that hinder nursing care for TB patients during the pandemic are related to precarious conditions of physical structures, social inequalities, failures in the implementation of the DOT and few material resources, however, there are strategies to face the demands and thus enhance the health promotion actions. Conclusion: This pathology preferentially affects individuals with lung injury, weakened immune system and individuals who are in a situation of poverty, which is directly related to the health-disease process, highlighting the need for action by the family health strategy and the nursing professional as a fundamental part in quality and integral assistance.